Tapeworms (Cestoda: Proteocephalidae) of Australian reptiles: hidden diversity of strictly host-specific parasites - de Chambrier, Alain; Beveridge, Ian; Scholz, Tomáš (Zootaxa, 2018)
Reptilian fauna of Australia is extraordinarily rich and diverse, but very little is known about parasites of reptiles, including proteocephalid cestodes of the genus Ophiotaenia La Rue, 1911. In the present survey, data on these parasites are summarised for the first time based on detailed evaluation of all available type and voucher specimens. This survey includes five named species, with four species redescribed, namely O. amphiboluri (Nybelin, 1917), O. longmani Johnston, 1916, O. mjobergi (Nybelin, 1917), and O. striata (Johnston, 1914), and 9 putative new species which are not formally described because of their poor quality and scarce material. An identification key is given for the five named species and unnamed species are briefly characterised with focus on their differential characteristics to facilitate their description as new taxa in the future. Australian species of Ophiotaenia form a monophyletic lineage, whose members share several morphological traits which are absent or rare in other proteocephalids, such as a three-layered embryophore, a scolex with large, anteriorly directed suckers, eggs with thick-walled embryophores, exclusively dorsal and paramuscular position of vitelline follicles, and a postequatorial to equatorial genital pore in most species. A new genus, Australophiotaenia, is proposed to accommodate the species from Australian reptiles that share the above-mentioned characters.